Lipoleiomyoma of the uterus in a woman of reproductive age (clinical case) - V.V. Talash; Ya.V. Palyokha; A.M. Gromova; V.V. Talash; V.B. Martynenko; N.O. Prylutska; N.I. Mityunina (Medičnì Perspektivi)
Uterine lipoleiomyoma is one of the variants of uterine leiomyoma, which is histologically represented by the presence of mature fat and smooth muscle cells. The relevance of the coverage of this clinical case is determined by the extreme rarity of the development of uterine lipoleiomyoma in women of reproductive age. The purpose of this work was to record this clinical case in the world statistics of lipoleiomyoma, to evaluate methods of diagnosis and differential diagnosis, to determine the role of early diagnosis of uterine lipoleioma in the subsequent tactics and scope of surgical treatment. Data from the medical records of a 41-year-old inpatient were analyzed. In addition to the generally accepted clinical and biochemical methods of blood and urine examination, electrocardiogram, ultrasound examination of the pelvic organs, the level of ovarian tumor markers in the blood (CA 125, HE4 and the ROMA index) was determined. The diagnosis of the disease was based on the data of pathohistological and immunohistochemical studies. Based on the results of a review of the medical literature, analysis of articles obtained as a result of a search of PubMed, SCOPUS, Web of Science, MedScape databases, the current state of the problem is highlighted, literary data related to the incidence, features of the clinical course, diagnosis and treatment of uterine lipoleiomyoma are summarized. The clinical case presented in the article demonstrates an incidental finding of a uterine lipoleiomyoma in a woman of reproductive age, measuring 30x25x20 cm, originated subserously from the body and cervix of the uterus, in the area of its isthmus. Under this condition, it occupied the entire Douglas space, the area of the sacro-uterine ligaments and the parietal peritoneum, intimately adjacent to the sigmoid and rectum, to the ureters and iliac vessels. The peculiarity of this clinical case is that sonographically uterine lipoleiomyoma was hidden under the "mask" of a dermoid cyst of the right ovary. Macroscopically, it differed from a typical lipoleiomyoma by the purple-bluish color of its outer surface and soot-colored, fine-lobed spongy structure on the section. The diagnosis of uterine lipoleiomyoma was verified only on the basis of pathohistological and immunohistochemical research. Microscopically, the lipoleiomyoma had a mesenchymal structure with a pronounced vascular component and consisted of mitotically inactive bundles of smooth muscle cells and mature adipocytes. Immunohistochemically, a positive reaction for caldesmon, desmin, smooth muscle actin alpha of tumor cells and for S.100 (DAKO, polyclonal) fatty cells was detected, which confirmed the hypothesis of direct transformation of smooth muscle cells existing in the leiomyoma of the uterus into fatty cells. This clinical case should complement the global statistical indicators of diagnosis of uterine lipoleiomyoma in women of reproductive age. Lipoleiomyoma should be considered as the primary diagnosis in case of detection of a large uterine tumor in women with excess body weight and be removed immediately after diagnosis, otherwise it is impossible to exclude its malignancy. For the planned diagnosis of neoplasms of the female genital organs, preference should be given to non-invasive research methods: magnetic resonance or computer tomography with contrast enhancement. The problem of these tumors lies in their unpredictable histogenesis, the unexpected presence of fat in the microscopic structure, and in the visual similarity to sarcomas. Verification of the diagnosis is carried out on the basis of pathohistological and immunohistochemical studies of the tumor preparation. Uterine lipoleioma can have a purplie-bluish color and develop by a broad base from the body and cervix of the uterus, as a result of "lipomatous" metaplasia of the uterine leiomyoma existing in a woman. Regular preventive examinations of women of all ages are crucial for timely detection of this rare neoplasm.